EVALUATION OF THE IMPLEMENTATION OF THE TAHFIZ AL-QUR'AN PROGRAM AT ASSHAFA ASSIGNING ISLAMIC ELEMENTARY SCHOOL, DEPOK - Nova FAUZIAH (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
This research aims to discover, develop and prove knowledge, while the specific objective is to disclose and analyse the implementation of tahfiz program, organizational procedures, manpower, infra structure, learning process, result and impact of implementation of Qur’an Tahfiz program in Asshafa Islamic School. This research is an evaluation by using DEM model (Discrepancy Evaluation Model). Data collection is done through observation, interview guidance and documentation. This research instrument is presented by Headmaster of Asshafa Islamic School, Vice Curriculum, Tahfiz Coordinator, Tahfiz Teacher, and School Committee. Data analysis techniques with data reduction (selecting and sorting data), display data, take conclusions and verification. The result of the research can be summarized as follows : (1) The program's conformity with program standards including curriculum, funding, infrastructure, and parental participation is implemented properly, (2) The tahfiz program at Asshafa Islamic Elementary School has been well planned, starting from the annual program, the semester program, scheduling, memorizing targets, to the methods that will be used in learning, (3) The tahfiz program at Asshafa Islamic Elementary School already has a fairly good evaluation system for students, (4) The results of the implementation of the Al-Qur'an tahfiz program at Asshafa Islamic Elementary School are related to the curriculum that is as expected, the principal through the deputy principal in the curriculum field can carry out planning, organizing, supervising, and controlling Tahfiz teachers and students can follow the program well.